2022
DOI: 10.3390/foods11081091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Highland Barley on Rheological Properties, Textural Properties and Starch Digestibility of Chinese Steamed Bread

Abstract: Highland barley has a different composition and structure to other crops. It has higher contents of total polyphenol (TPC), total flavonoid (TFC) and β-glucan, which can be supplemented to improve the nutrition of wheat-flour-based food. In this study, the flours of three different grain-colored highland barley varieties Beiqing 6 (BQ), Dulihuang (DLH), and Heilaoya (HLY), were added to Jimai60 (JM, a wheat variety with medium gluten) wheat flour at different substitution levels to investigate their effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 73 publications
0
6
1
Order By: Relevance
“…Our results showed that the TPC of HBP extract was 1016.16 ± 3.81 µg FAE/mL. A previous study showed that the TPC of 12 blue highland barley was 336.21 to 453.94 mg GAE/100 g DW (40). The inconsistent results may be due to the different methods for estimation of TPC.…”
Section: Discussioncontrasting
confidence: 59%
“…Our results showed that the TPC of HBP extract was 1016.16 ± 3.81 µg FAE/mL. A previous study showed that the TPC of 12 blue highland barley was 336.21 to 453.94 mg GAE/100 g DW (40). The inconsistent results may be due to the different methods for estimation of TPC.…”
Section: Discussioncontrasting
confidence: 59%
“…As flavonoids and β‐glucan play an active role in reducing blood lipids, blood pressure and blood glucose, it can be inferred that the glutinous rice cakes made with tartary buckwheat and highland barley have strong biological activity with high nutritional value (Luthar et al ., 2021). In support of this, in another study, a high content of total flavonoids and β‐glucan in Chinese steamed bread (made with highland barley flour along with regular wheat flour) resulted in low starch digestibility, and significantly improved nutritional quality (Wu et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Mineral water was offered between samples. Hardness (thirty points), springiness (fifteen points), taste (twenty points), structure (fifteen points) and flavour (twenty points) of the glutinous rice cakes were scored (Wu et al ., 2022). One hundred points was set as total score, and the evaluators' scores reflected their overall sensory evaluation of the glutinous rice cakes.…”
Section: Methodsmentioning
confidence: 99%
“…Highland barley flour (HBF) is typically used in composite flour for steamed bread, noodles, chapatti, chiffon cake, and biscuits in recent years (Ruan et al ., 2019; Deng et al ., 2020) because it is hard to form a dough independently (Wu et al ., 2022). Its incorporation level in composites was recommended to be lower than 30% HBF to develop consumer‐acceptable products (Hong et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Its incorporation level in composites was recommended to be lower than 30% HBF to develop consumer‐acceptable products (Hong et al ., 2021). It was used at 20% and 30% in composite flour for bread and steamed bread, respectively (Al‐Ansi et al ., 2022; Wu et al ., 2022). Extruded HBF, pre‐gelatinized HBF, and sodium alginate were used in the development of yellow alkaline noodles and white salted noodles, which increased the substitution ratio of HBF to 40% and 60%, respectively (Zhang et al ., 2016; Tuersuntuoheti et al ., 2019; Hong et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%